Compressibility and Strength of Natural and Steel Slag Treated Gypseous Soil - Jassam, Mahmood G.; Hussein, Israa S.; Ismail, Aodai A.; Ameen, Aynoor N. (Engineering, Technology & Applied Science Research, 2025)
Significant portions of the Earth’s surface are covered with soils, and when they eventually get saturated with water, they may experience significant changes in volume. These materials are called collapsible soils. Gypsum rocks are formed as a result of the evaporation of salt water from lakes formed in desert or semi-desert areas. The implication of steel slag as a modifier on the compressibility and shear strength of gypseous soil was investigated in this work. Samples of soil with a 53.36% gypsum concentration were acquired from Tikrit, located in the Salahaldeen province of Iraq. Steel slag was added in proportions of 3%, 6%, 9%, 12%, and 15% by weight of the soil. Collapse and direct shear tests were conducted for both natural and treated samples. According to the research findings, the treated soil has significantly higher degree of cohesion and an angle of internal friction, and the Collapse Potential (CP) value has substantially dropped. This enhancement can reach up to 69.28% at 15% treatment for collapse potential, which represents the best weight ratio for the additive. The cohesion and angle of internal friction increased to 155.41% and 82.0%, respectively, with 15% treatment for the direct shear test.